Assessment of Pedestrian Crossing Bridge Safety: Case Study Sungai Panas, Batam - Deon Libora; Indrastuti Indrastuti (LEADER: Civil Engineering and Architecture Journal, 2023)
This study aims to assess the impact of pedestrian overhead crossing bridges on pedestrian safety in the Sungai Panas subdistrict of Batam City. The construction of these pedestrian crossing bridges in the area aims to improve accessibility and safety for pedestrians crossing busy roads. The research methodology involves field surveys to gather data on the usage of pedestrian crossing bridges, pedestrian behavior, and the incidence of pedestrian accidents before and after the construction of the overhead crossing bridges. Additionally, data on traffic speeds on the relevant roadways are also collected. The results of this study indicate that the construction of the pedestrian overhead crossing bridges has enhanced pedestrian safety in the Sungai Panas subdistrict. The number of pedestrians using the crossing bridges has significantly increased following the construction, while the number of pedestrian accidents has experienced a notable decrease. Furthermore, the traffic speeds on the associated roadways also show a decrease after the construction of the pedestrian crossing bridges. The conclusion drawn from this research is that pedestrian crossing bridges have a positive impact on pedestrian safety in the Sungai Panas subdistrict of Batam City. This study can serve as a reference for the government and relevant authorities to consider further development of pedestrian crossing bridges in areas with heavy traffic to enhance pedestrian safety. Additionally, this research provides valuable insights into the importance of safe and pedestrian-friendly infrastructure in planning sustainable urban development.